The Gamifikasi Pembelajaran Berbasis Quizizz Sebagai Upaya Peningkatan Kompetensi Pemanfaatan Teknologi Pengajar - Aisyiah Al Adawiyah; Akbar Syamsul Arifin; Dany Buyung Yudha Prasetya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Post-pandemic, the implementation of IT makes learning more creative, innovative, and interactive. The presence of interaction and collaboration between students through ICT-based learning means is important for them to become enthusiastically engaged in learning. With the development of technology, educators must have knowledge and skills in using IT to support learning in the smart society era. However, based on the basic research conducted by one of the students of the SMA Negeri 8 Semarang department, the department found that there is still no optimal way to use ICT as a means of learning due to the time it takes to prepare materials. learning is limited. On the other hand, thanks to Quizizz, preparing to use it does not take much time because Quizizz offers many different features to help teachers learn more easily. Quizizz is a game-based educational app that features fun and free games that entertain you during the learning process. Quizizz training aims to ensure that teachers have equal opportunities to maximize learning using ICT-based media, so that Quizizz can be a solution embedded in the learning media creation framework. IT-based learning takes a lot of time to create an accessible, student-centered environment. The classroom atmosphere in the development of critical thinking (critical thinking), cooperation (collaboration), communication (communication) and creativity (creativity) are called the 4Cs.